2019
DOI: 10.3892/ijo.2019.4840
|View full text |Cite
|
Sign up to set email alerts
|

CXCL1 stimulates migration and invasion in ER‑negative breast cancer cells via activation of the ERK/MMP2/9 signaling axis

Abstract: Chemokine (C-X-C motif) ligand 1 (CXCL1), a member of the CXC chemokine family, has been reported to be a critical factor in inflammatory diseases and tumor progression; however, its functions and molecular mechanisms in estrogen receptor α (ER)-negative breast cancer (BC) remain largely unknown. The present study demonstrated that CXCL1 was upregulated in ER-negative BC tissues and cell lines compared with ER-positive tissues and cell lines. Treatment with recombinant human CXCL1 protein promoted ER-negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 54 publications
4
54
0
Order By: Relevance
“…The Cxcl1 gene encodes chemokine (C-X-C motif) ligand 1, which is a member of the chemokine family involved in inflammation and tumor progression (Dhawan and Richmond, 2002). Cxcl1 is up-regulated in ERa-negative breast cancer and stimulates migration and tumor invasiveness through Erk1/2 activation (Yang et al, 2019). Breast cancers with overexpression of CXCL1 have increased propensity for survival at metastatic sites and demonstrate chemoresistance (Acharyya et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The Cxcl1 gene encodes chemokine (C-X-C motif) ligand 1, which is a member of the chemokine family involved in inflammation and tumor progression (Dhawan and Richmond, 2002). Cxcl1 is up-regulated in ERa-negative breast cancer and stimulates migration and tumor invasiveness through Erk1/2 activation (Yang et al, 2019). Breast cancers with overexpression of CXCL1 have increased propensity for survival at metastatic sites and demonstrate chemoresistance (Acharyya et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that CXCL1 could promote the progression of cancer by activating multiple signaling pathways. Yang et al revealed that high expression of CXCL1 stimulated breast cancer cell metastasis via the ERK/MMP2/9 pathway [12]. Wang et al discovered CXCL1 promoted breast cancer metastasis via NF-kB/SOX4 activation [18].…”
Section: Discussionmentioning
confidence: 99%
“…CXCL1 binds speci cally to the CXC chemokine receptor 2 (CXCR2), which is a member of the G protein-coupled receptor superfamily [9]. Previous investigations have demonstrated CXCL1 expression might play an essential role in the chemoresistance, tumorigenesis, metastasis and angiogenesis of cancer [10][11][12][13]. In recent years, previous studies had explored the prognostic effects of CXCL1 in cancers [14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…MMP-2 and 9 are regarded as markers of metastatic potential in malignancies (39). The level of these two markers were evaluated in 4T1 cells following treatment with H 2 O 2 or H 2 O 2 + HA as oxygen source.…”
Section: Evaluation Of Tumour Metastatic Potentialmentioning
confidence: 99%